Relevance of GC content to the conservation of DNA polymerase III/mismatch repair system in Gram-positive bacteria - Akashi, Motohiro; Yoshikawa, Hirofumi (Frontiers in Microbiology, 2013)
The mechanism of DNA replication is one of the driving forces of genome evolution. Bacterial DNA polymerase III, the primary complex of DNA replication, consists of PolC and DnaE. PolC is conserved in Gram-positive bacteria, especially in the Firmicutes with low GC content, whereas DnaE is widely conserved in most Gram-negative and Gram-positive bacteria. PolC contains two domains, the 3′-5′ exonuclease domain and the polymerase domain, while DnaE only possesses the polymerase domain. Accordingly, DnaE does not have the proofreading function; in Escherichia coli, another enzyme DnaQ performs this function. In most bacteria, the fidelity of DNA replication is maintained by 3′-5′ exonuclease and a mismatch repair (MMR) system. However, we found that most Actinobacteria (a group of Gram-positive bacteria with high GC content) appear to have lost the MMR system and chromosomes may be replicated by DnaE-type DNA polymerase III with DnaQ-like 3′-5′ exonuclease. We tested the mutation bias of Bacillus subtilis, which belongs to the Firmicutes and found that the wild type strain is AT-biased while the mutS-deletant strain is remarkably GC-biased. If we presume that DnaE tends to make mistakes that increase GC content, these results can be explained by the mutS deletion (i.e., deletion of the MMR system). Thus, we propose that GC content is regulated by DNA polymerase and MMR system, and the absence of polC genes, which participate in the MMR system, may be the reason for the increase of GC content in Gram-positive bacteria such as Actinobacteria.